Morvan Syndrome Secondary to Thymic Carcinoma in a Patient with Systemic Lupus Erythematosus - Gabrielle Macaron; Elie El Rassy; Salam Koussa (Case Reports in Neurological Medicine)
Morvan syndrome (MoS) is a rare paraneoplastic autoimmune disorder characterized by peripheral nerve hyperexcitability, autonomic dysfunction, and sleep disorders. Systemic lupus erythmatosus (SLE) cooccurs in 6–10% of patients with thymoma. It may occur before, concurrently with, or after thymoma diagnosis. This paper reports the first case of cooccurrence of SLE, thymic carcinoma, and MoS. The cooccurrence of SLE, thymoma, and MoS delineates the generalized autoimmunity process. Symptoms of both MoS and SLE abated upon tumor resection.